Patient preferences for heart valve disease intervention - Simon Fifer; Brittany Keen; Polo Guilbert‐Wright; Kaoru Yamabe; Dale J. Murdoch (Health Expectations)
Abstract Background This study aimed to determine how patients trade‐off the benefits and risks of two different types of procedures used to treat heart valve disease (HVD). It also aimed to determine patients' preferences for HVD treatments (predicted uptake) and the relative importance of each treatment attribute. Methods A discrete choice experiment (DCE) was conducted in Australia and Japan with patients who required a heart valve procedure. Patients were stratified into three categories: no prior procedure experience, minimally invasive procedure experience and invasive procedure experience. DCE attributes included risk of mortality; risk of stroke; needing dialysis; needing a new pacemaker; valve durability; independence 1 month after surgery; and out‐of‐pocket expenses. Participants chose between two hypothetical labelled approaches to therapy (‘invasive procedure’ and ‘minimally invasive procedure’), with a separate opt‐out included. A mixed multinomial logit model was used to analyse preferences. Results The DCE was completed by 143 Australian and 206 Japanese patients. Both populations demonstrated an overall preference for the minimally invasive procedure over the invasive procedure. All attributes tested significantly predicted choice and were important to patient decision‐making. However, patients' choices were most influenced by the durability of the valve and the likelihood of independence postprocedure, irrespective of their prior procedure experience. Differences in preference were observed between Australian and Japanese patients; valve durability was the most important attribute among Australian patients, while Japanese patients emphasised regaining independence postsurgery. Risk of mortality was less important relative to other key attributes in Japan; however, it remained significant to the model. Conclusions HVD patients prefer a minimally invasive procedure over an invasive procedure, irrespective of prior treatment experience. Key attributes contributing to treatment preferences are valve durability and faster recovery. These results can be used to help inform healthcare decision‐makers about what features of heart valve procedures patients value most. Patient and Public Contribution People with lived experience of HVD were included in multiple stages of the design phase of this research. First, patients and doctors were consulted by taking part in qualitative interviews. The qualitative interviews helped inform which treatment attributes to include in the DCE based on what was important to those with lived experience and those who help make treatment decisions on behalf of patients. Qualitative interview participants also assisted with the framing of questions in the online survey to ensure the terminology was patient‐friendly and relevant to those with lived experience. Following qualitative interviews, the DCE attribute list was agreed on in expert consultation with a steering committee, which included patient representatives and treating physicians (interventional cardiologists, cardiothoracic surgeons). The survey was also pilot tested with a small sample of patients and minor adjustments were made to the wording to ensure it was appropriate and meaningful to those with lived experience of HVD.